Explainable AI for Audio and Visual Affective Computing: A Scoping Review - Johnson, David; Hakobyan, Olya; Paletschek, Jonas; Drimalla, Hanna (IEEE Transactions on Affective Computing)
ffective computing often relies on audiovisual data to identify affective states from non-verbal signals, such as facial expressions and vocal cues. Since automatic affect recognition can be used in sensitive applications, such as healthcare and education, it is crucial to understand how models arrive at their decisions. Interpretability of machine learning models is the goal of the emerging research area of Explainable AI (explainable AI (XAI)). This scoping review aims to survey the field of audiovisual affective machine learning to identify how XAI is applied in this domain. We first provide an overview of XAI concepts relevant to affective computing. Next, following the recommended PRISMA guidelines, we perform a literature search in the ACM, IEEE, Web of Science and PubMed databases. After systematically reviewing 1190 articles, a final set of 65 papers is included in our analysis. We quantitatively summarize the scope, methods and evaluation of the XAI techniques used in the identified papers. Our findings show encouraging developments for using XAI to explain models in audiovisual affective computing, yet only a limited set of methods are used in the reviewed works. Following a critical discussion, we provide recommendations for incorporating interpretability in future work for affective machine learnin

What you need to know about a learning robot: Identifying the enabling architecture of complex systems - Beierling, Helen; Richter, Phillip; Brandt, Mara; Terfloth, Lutz; Schulte, Carsten; Wersing, Heiko; Vollmer, Anna-Lisa (Cognitive Systems Research)
Nowadays we deal with robots and AI more and more in our everyday life. However, their behavior is not always apparent to most lay users, especially in error situations. This can lead to misconceptions about the behavior of the technologies being used. This in turn can lead to misuse and rejection by users. Explanation, for example through transparency, can address these misconceptions. However, explaining the entire software or hardware would be confusing and overwhelming for users. Therefore, this paper focuses on the ‘enabling’ architecture. It describes those aspects of a robotic system that may need to be explained to enable someone to use the technology effectively. Furthermore, this paper deals with the ‘explanandum’, i.e. the corresponding misunderstandings or missing concepts of the enabling architecture that need to be clarified. Thus, we have developed and are presenting an approach to determine the ‘enabling’ architecture and the resulting ‘explanandum’ of complex technologies.
Keywords: Robotics HRI Explainability Didactics Didactic reconstruction

Advancing Human-Robot Collaboration: The Impact of Flexible Input Mechanisms - Beierling, Helen; Loos, Kira; Helmert, Robin; Vollmer, Anna-Lisa
This position paper calls for an increase in the number and flexibility of input mechanisms in user-robot in- teractions, highlighting their potential to enhance learning algo- rithms through user feedback. Moreover, we argue that refining interfaces, interactions, and systems is crucial for the optimal integration of mechanisms into learning processes. Our call to research involves the development of interfaces that enable flexible mechanisms, and the mechanisms interactions can benefit most from, and the algorithmic incorporation of user input. This aims to advance the adaptability and responsiveness of robotic systems in human-centric environments

Influence of Dispersion Gas and Resulting Reaction Zone on the Particle Formation in Spray Flame Synthesis (Presentation) - Massopo, Orlando; Schmid, Hans-Joachim; Reddemann, Manuel; Kneer, Reinhold; Bieber, Malte

Untersuchung des Lösungsmitteleinflusses auf die Synthese von Manganoxid-Nanopartikeln in der Flammenspraypyrolyse - Zink, Timm Florian; Massopo, Orlando; Jesinghausen, Steffen; Schmid, Hans-Joachim

Einfluss der Zerstäubungsparameter auf die Partikelbildung und die Eigenschaften der Endproduktpulver (Studienarbeit) - El Gabbouhi, Abderazzak; Massopo, Orlando; Jesinghausen, Steffen; Schmid, Hans-Joachim

Understanding and Improving Triplet Exciton Transfer in Sensitized Silicon Solar Cells - Krenz, Marvin; Sanna, Simone; Gerstmann, Uwe; Schmidt, Wolf Gero (The Journal of Physical Chemistry C)

"Was heißt das, Mama?" Die Familie als Ort von Sprachaneignung und mehrsprachigen Praktiken am Beispiel einer türkisch-deutsch-sprachigen Familie - Ballweg, Sandra (Zeitschrift für Interaktionsforschung in DaFZ)

Blockchain Governance - Reijers, Wessel; de Filippi, Primavera; Mannan, Morshed

The role of interactive gestures in explanatory interactions - Lohmer, Vivien; Kern, Friederike (Second International Multimodal Communication Symposium (MMSYM) - Book of Abstract)
Keywords: gesture; explanations; conversation analysis

Investigation of the influence of the rivet geometry on joint formation for a versatile self-piercing riveting process - Kappe, Fabian; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part E: Journal of Process Mechanical Engineering)
Climate change has led to a large number of countries deciding to reduce carbon dioxide (CO 2 ) emissions significantly. As the mobility sector is a major contributor to CO 2 , various strategies are being pursued to achieve the climate targets set. An increasingly applied lightweight design method is the use of multi-material constructions. To join these structures, mechanical joining technologies such as self-pierce riveting are being used. As a result of the currently rigid tool systems, which cannot react to changing boundary conditions, a large number of rivet–die combinations is required to join the rising number of materials as well as material thickness combinations. Thus, new, versatile joining technologies are needed that can react to the described changes. The versatile self-piercing riveting (V-SPR) process is one possible approach. In this process, different material thicknesses can be joined by using a multi-range capable rivet which is set by a joining system with extended actuator technology. In this study, the V-SPR joining process is analysed numerically according to the influence of the geometrical rivet parameters on the joints characteristics as well as the resulting material flow. The investigations showed that the shank geometry has a decisive influence on the expansion of the rivet. Furthermore, the rivet length could be proven to be an influencing factor. By changing the head radii and the protrusion height, the forming behaviour of the rivet head onto the punch-sided joining part could be improved and thus the formation of air pockets was prevented. Based on the numerical investigations, a novel rivet geometry was developed and produced by machining. Subsequently, experimentally produced joints were analysed according to their joint formation and load-bearing capacity.

Influence of the process time on a self-piercing riveting process with tumbling kinematic - Wituschek, Simon; Elbel, Leonie; Lechner, Michael (Proceedings of the Institution of Mechanical Engineers, Part E: Journal of Process Mechanical Engineering)
The increasing significance of ecological responsibility, stricter political regulations and economic objectives are driving innovation in research fields such as lightweight construction. One of the most important popular methods is the use of multi-material systems. Due to the different geometric and mechanical properties of the various materials used, resource efficient applications and utilizations are possible. Great challenges arise for the joining processes to realize these multi-material systems, since conventional joining processes reach their limits. In the field of mechanical joining processes, there are continuously new approaches, such as superimposing the punch in a self-piercing riveting process with a tumbling kinematic, to increase the number of adaptable process parameters and enhance the process control. Through various preliminary tests, a good understanding of the process has been developed, which allows to directly control the geometric joint parameters by configuring the tumbling strategy. A major challenge, particularly with regard to future industrial applications, is the process time, which is comparatively high due to the tumbling kinematics. In the investigations, a reduction of approximately 90% of the process time is targeted by adapting the joining and tumbling strategy. Therefore, the correlation of the traverse velocity and the tumbling velocity are examined in a gradual series of experiments. To represent realistic applications, the experiments are carried out with a dual-phase steel and a precipitation-hardening aluminum alloy. For identifying the influence of the process parameters on the joining process, a constant rivet–die combination is applied. Further, the examination of force–displacement curves is conducted. Moreover, the determination of geometric joint parameters is reliant upon macrographs to assess the influence of the joining time on the geometric joint formation. The test results show that a significant increase in joining speed with a resulting reduction in process time is feasible. Although the joining properties are affected, reliable joining is possible. In particular, the shaft thickness of the rivet is influenced by the varying proportion of the tumbling process in the joining operation and increases with higher joining speeds.

Investigation on the load-bearing capacity and joint formation of hybrid functional components joined by orbital forming - Hetzel, A.; Wituschek, Simon; Römisch, D.; Sippel, F.; Lechner, M.; Merklein, M. (Proceedings of the Institution of Mechanical Engineers, Part E: Journal of Process Mechanical Engineering)
Increasing material costs, decreasing availability, and ever-higher demands on environmental compatibility and complexity require new strategies in the development and production of functional components. Consequently, a combined approach from the areas of design, material science, and manufacturing is mandatory, in order to meet the requirements. Reducing the number of parts, using lightweight materials and applying hybrid components with a multimaterial mix are possible solutions. Nevertheless, conventional joining operations like welding or riveting are reaching their limits in terms of material utilization, load-bearing capacity as well as versatility of the process. Thus, innovative and versatile joining by forming operations and process combinations are focus of current research. In this context, the innovative process of orbital forming had been investigated as a joining by forming operation to manufacture load-adapted hybrid functional components. By tilting of one tool component during the process, a radial material flow is generated, allowing the crimping of the two joining partners. Nevertheless, the load-bearing capacity in axial direction could be identified as limiting factor for a possible application. Therefore, the aim of this investigation is the development of a fundamental process understanding on the influence of a novel geometrical adaption of the joint on the resulting load bearing capacity. The influence of varying geometrical proportions of the joint on the quality is evaluated, considering the form filling, the geometrical properties of the components as well as the maximum transmittable axial load. As joining partners, the dual-phase steel DP600 and the aluminum alloy EN AW-5754 with a thickness of 2.0 mm are used.

Influence of local heat treatment of rivets on the joint formation of a versatile joining process - Kappe, Fabian; Bobbert, Mathias; Meschut, Gerson (IOP Conference Series: Materials Science and Engineering)
Abstract An efficient lightweight construction method is the combination of different materials in order to adapt the structure to the applied load. To join these multi-material structures mechanical joining technologies are applied. However, the rigid tooling systems cannot be adjusted to changing boundary conditions which is why new, versatile joining technologies are required. In the versatile self-piercing riveting (V-SPR) process presented in [1] different material combination are joined by using a multi-range capable rivet. The rivet head is formed onto the respective thickness of the joint by an outer punch. In order to punch thru the upper sheet a great rivet hardness is required whereas a lower hardness is required for the subsequent forming of the rivet head. To achieve a combination of these requirements, this study investigates a local heat treatment of the rivet. The aim is to determine the feasibility of such a heat treatment as well as to investigate the influence on the joint formation.

Revealing the Dynamics of Medical Diagnostic Reasoning as Step-by-Step Cognitive Process Trajectories - Battefeld, Dominik; Mues, Sigrid; Wehner, Tim; House, Patrick; Kellinghaus, Christoph; Wellmer, Jörg; Kopp, Stefan (Proceedings of the 46th Annual Conference of the Cognitive Science Society)
A detailed understanding of the cognitive process underlying diagnostic reasoning in medical experts is currently lacking. While high-level theories like hypothetico-deductive reasoning were proposed long ago, the inner workings of the step-by-step dynamics within the mind remain unknown. We present a fully automated approach to elicit, monitor, and record diagnostic reasoning processes at a fine-grained level. A web-based user interface enables physicians to carry out a full diagnosis process on a simulated patient, given as a pre-defined clinical vignette. By collecting the physician’s information queries and hypothesis revisions, highly detailed diagnostic reasoning trajectories are captured leading to a diagnosis and its justification. Four expert epileptologists with a mean experience of 19 years were recruited to evaluate the system and share their impressions in semi-structured interviews. We find that the recorded trajectories validate proposed theories on broader diagnostic reasoning, while also providing valuable additional details extending previous findings.
Keywords: Differential Diagnosis; Diagnostic Reasoning; Reasoning Process Analysis; Seizure; Epilepsy

A Study on Integrating Representational Gestures into Automatically Generated Embodied Explanations - Robrecht, Amelie Sophie; Voss, Hendric; Gottschalk, Lisa; Kopp, Stefan (Proceedings of the ACM International Conference on Intelligent Virtual Agents)

Inferring Partner Models for Adaptive Explanation Generation - Robrecht, Amelie; Buhl, Heike M.; Kopp, Stefan (Proceedings of the 28th Workshop on the Semantics and Pragmatics of Dialogue)

Anstieg der Energieaufnahme von Haushaltskältegeräten - Kruse, Simon; Elsner, Andreas; Paul, Andreas; Kasper, Tina
Keywords: Haushaltskältegeräte; Energieaufnahme; Alterung

Ermittlung von Flammentemperaturen mittels Thermoelementen in transienten Messungen (Poster) - Wortmeier, Andreas; Gonchikzhapov, Munko; Kasper, Tina

The True Story Of A Total Fake: Identitätsfragen mit der Netflix Serie Inventing Anna unterrichten - Intveen, Julie (Fernsehserielles Erzählen im fächerübergreifenden Unterricht: Forschungs- und unterrichtspraktische Perspektiven)